2x(x+e)=3e(x+e)

Simple and best practice solution for 2x(x+e)=3e(x+e) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x(x+e)=3e(x+e) equation:


Simplifying
2x(x + e) = 3e(x + e)

Reorder the terms:
2x(e + x) = 3e(x + e)
(e * 2x + x * 2x) = 3e(x + e)
(2ex + 2x2) = 3e(x + e)

Reorder the terms:
2ex + 2x2 = 3e(e + x)
2ex + 2x2 = (e * 3e + x * 3e)

Reorder the terms:
2ex + 2x2 = (3ex + 3e2)
2ex + 2x2 = (3ex + 3e2)

Solving
2ex + 2x2 = 3ex + 3e2

Solving for variable 'e'.

Reorder the terms:
2ex + -3ex + -3e2 + 2x2 = 3ex + 3e2 + -3ex + -3e2

Combine like terms: 2ex + -3ex = -1ex
-1ex + -3e2 + 2x2 = 3ex + 3e2 + -3ex + -3e2

Reorder the terms:
-1ex + -3e2 + 2x2 = 3ex + -3ex + 3e2 + -3e2

Combine like terms: 3ex + -3ex = 0
-1ex + -3e2 + 2x2 = 0 + 3e2 + -3e2
-1ex + -3e2 + 2x2 = 3e2 + -3e2

Combine like terms: 3e2 + -3e2 = 0
-1ex + -3e2 + 2x2 = 0

Factor a trinomial.
(-1e + -1x)(3e + -2x) = 0

Subproblem 1

Set the factor '(-1e + -1x)' equal to zero and attempt to solve: Simplifying -1e + -1x = 0 Solving -1e + -1x = 0 Move all terms containing e to the left, all other terms to the right. Add 'x' to each side of the equation. -1e + -1x + x = 0 + x Combine like terms: -1x + x = 0 -1e + 0 = 0 + x -1e = 0 + x Remove the zero: -1e = x Divide each side by '-1'. e = -1x Simplifying e = -1x

Subproblem 2

Set the factor '(3e + -2x)' equal to zero and attempt to solve: Simplifying 3e + -2x = 0 Solving 3e + -2x = 0 Move all terms containing e to the left, all other terms to the right. Add '2x' to each side of the equation. 3e + -2x + 2x = 0 + 2x Combine like terms: -2x + 2x = 0 3e + 0 = 0 + 2x 3e = 0 + 2x Remove the zero: 3e = 2x Divide each side by '3'. e = 0.6666666667x Simplifying e = 0.6666666667x

Solution

e = {-1x, 0.6666666667x}

See similar equations:

| 162=2xsquared | | 4s^2+19=12s | | x/y=2.727272 | | 10x-x^2=5 | | 10x-y^2=5 | | 3+4x-10=17 | | N(14+6)=22 | | (a+1)(a*2+3a+1)= | | x^2-61.28x=2000 | | 15+3y=51-y-y-y | | 16-7m=30 | | 5-3y+5y=-8+6+9y | | -(x-1)=x-5 | | 64-32y=55-35y | | 27=5-2x | | 7+91x=52x+3 | | -2(x-5)=10-3x | | 6x-3x(x-1)=21 | | 2x^2+2y-1=0 | | 2cosx+4sinx=3 | | 16x-5y=125 | | 2y-4=29 | | y^2+11y+49=4 | | x((3x-3)(2x-8)+(2x+2)(3x+1))=(5x-5)(3x+1)(2x-8) | | ln(x)=-x+2 | | x^2+y^2-2y=3 | | 20log(3x)=49 | | 4.5=4.125 | | X^2+11X-450=0 | | 3x^4/x^2-9 | | 18(6)+x=134 | | 2x^2-4y-1=0 |

Equations solver categories